2020
DOI: 10.3390/jcm9072244
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Changes in Patients with COVID-19: A Meta-Analysis with Meta-Regressions

Abstract: Background: Complications of coronavirus disease 2019 (COVID-19) include coagulopathy. We performed a meta-analysis on the association of COVID-19 severity with changes in hemostatic parameters. Methods: Data on prothrombin time (PT), activated partial thromboplastin time (aPTT), D-Dimer, platelets (PLT), or fibrinogen in severe versus mild COVID-19 patients, and/or in non-survivors to COVID-19 versus survivors were systematically searched. The standardized mean difference (SMD) was calculated. Results: Sixty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 149 publications
(357 reference statements)
1
36
0
7
Order By: Relevance
“…Results of raised D-Dimer levels, in the present study, are consistent with different studies that showed higher D-Dimer levels in expired COVID-19 patients compared to survive. 17,[26][27][28][29][30] Elevated Ddimer level is a risk factor for the development of DVT or pulmonary embolism and can predict both severity and mortality. 2,31,32 British Thoracic Society, based on risk stratification, suggested prophylactic low dose heparin in COVID patients with D-dimer more than 3000 ng/ml, while D-dimer more than 1000 ng/ml is an independent risk factor for the critical disease.…”
Section: Discussionmentioning
confidence: 99%
“…Results of raised D-Dimer levels, in the present study, are consistent with different studies that showed higher D-Dimer levels in expired COVID-19 patients compared to survive. 17,[26][27][28][29][30] Elevated Ddimer level is a risk factor for the development of DVT or pulmonary embolism and can predict both severity and mortality. 2,31,32 British Thoracic Society, based on risk stratification, suggested prophylactic low dose heparin in COVID patients with D-dimer more than 3000 ng/ml, while D-dimer more than 1000 ng/ml is an independent risk factor for the critical disease.…”
Section: Discussionmentioning
confidence: 99%
“…The association of COVID-19 infection severity with changes in hemostatic parameters was explored in a meta-analysis of 60 studies comparing 5487 patients with severe and 9670 patients with mild COVID-19 infection. 42 The meta-analysis found a higher prothrombin time (PT) (standardized mean difference-SMD: 0.41), D-dimer (SMD: 0.67), and fibrinogen values (SMD: 1.84), with lower platelet count (SMD: -0.74) among severe infection patients. Analysis of 25 studies on 1511 COVID-19 non-survivors and 6287 survivors showed higher PT (SMD: 0.67) and D-Dimer values (SMD: 3.88), with lower platelet count (SMD: -0.60) among non-survivors.…”
Section: Hypercoagulable Statementioning
confidence: 99%
“…Therefore, other auxiliary tests combining clinical, molecular, and radiological features would be beneficial for diagnosis. In clinical, COVID-19 is mostly characterized by inflammatory exudative pulmonary lesions with symptoms including fever, dry cough, headache, myalgia, breathlessness, and asthenia [14,15]. Although clinical tests are essential for diagnosis, the symptoms of patients at the early stage of COVID-19 could not be differentiated from common viral pneumonia.…”
Section: Introductionmentioning
confidence: 99%